Ion beam elemental analysis of doped Si02 optical fibre and its thermoluminescence response when irradiated with protons - Ramli, Ahmad Termizi (Academy of Sciences Malaysia, 2010)

(untitled)
This research was focused on the thermoluminescence (TL) response of commercially produced single-mode telecommunication optical fibre manufactured by INOCORP (Canada). The fibres were either in the form of pure silica (SiO2) or as SiO2 doped with Ge or Al at concentrations appropriate for total internal reflection, as required for telecommunication purposes. Each of these INOCORP fibres had a core diameter of 125 ± 0.1 µm. It was noted that dopant concentration was not included among the data provided in the accompanying product data sheet. A particularly important parameter for obtaining the highest TL yield in this study was the dopant concentration of the SiO2 fibre. The dopants tended to diffuse during the production of the optical fibre. To obtain this parameter, proton induced X-ray emission (PIXE) analysis was utilised. PIXE while having limited depth resolution could unambiguously identify elements and analyse trace elements with a detection limit approaching µg g–1. For Al-doped fibres, dopant concentrations in the range of 0.98 – 2.93 mol% had been estimated, the equivalent range for Ge-doped fibres was 0.53 – 0.71 mol%. A linear dose response was observed following 2.5 MeV proton irradiation for Ge- and Al-doped fibres for up to 7 min exposure.